DHAHIRATU AL-ISTIKHDAM AL-SHUROH AL-RUMZIYAH FI MAWAQI AL-TAWASHUL AL-IJTIMAI’I WA DAURIHA FI AL-TA’THILI AL-LUGHAWI LADA THALABAH AQSAM AL-LUGHAH AL-ARABIYAH FI JAMIAH AL-JAUFI - Ata, Ahmad Ibrahim Bani (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2020)
This study aims to analyze the use of symbols in social media and its impact on the language among students of the Arabic language program at Jouf University. Youth category is the largest group exposed to linguistic decline because of being hooked on social media. This has created negative impressions of their language, as a generation may emerge far from his language and identity, unable to express, the transition from verbal symbols to symbolic leads to shifts in meaning and function, and the reduction of sensations in the yellow faces (emoticons). These symbols serve only general purposes, initial and superficial connotations, simple words and sentences. The use of language in everyday conversations to communicate with relatives and entertainment is one of the most motivating habits of language revolt, especially the positive impression it has left on young people for their ease of expression, attractiveness and simplicity, effortless, shortening speech, and modernity, all of which led to dumping in their language use. It can, therefore, lead to the development of encrypted language dictionaries, change the pattern of thinking, hasten the formation of false personal impressions, and lead to introverts and psychological isolation; therefore, young people fall victim to linguistic decay.